Olive Oil and Basketball: On Collective Memory and America’s Troubled Alliances with the Philippines and Thailand - Greg Raymond (Journal Of Global Strategic Studies, 2022)
United States’ alliances in Southeast Asia are troubled. This paper argues that dominant frameworks for understanding alliance dynamics, which assume that rational calculation and bargaining are the primary sources of alliance dynamics, are inadequate for explaining the fragility of US alliances with Thailand and the Philippines. It proposes that a constructivist perspective, emphasising identity, emotion, and collective memory, offers a useful supplementary lens for explaining why some alliances experience turbulence. The paper sets out the theoretical case for examining collective memory in an alliance context, together with a methodology for practical application. The paper finds that in the US-Thai alliance, the domestic politics of collective memory has constrained commemoration of highpoints in the longstanding US-Thai military partnership, leaving the alliance with weaker public support and more vulnerable to strains than would otherwise have been the case. In the Philippines, state sanctioned narratives recognising shared sacrifice during the Second World War are counterbalanced by traumatic memories of the United States-Philippines colonial war, producing a deep ambivalence. These results point to the need for more systematic analysis of collective memory as an important variable in international politics.